The classical tradition in modern American fiction - Roynon, Tessa 1974- (BAAS paperbacks, 2021)
This book is an invaluable survey of the allusions to ancient Greek and Roman culture in the work of seven major modern American novelists: Willa Cather, F. Scott Fitzgerald, William Faulkner, Ralph Ellison, Toni Morrison, Philip Roth and Marilynne Robinson